Routes, destinations and delays: recent advances in AMPA receptor trafficking - Henley, Jeremy M.; Barker, Ellen A.; Glebov, Oleg O. (Trends in neurosciences (Regular ed.), 2011)
Postsynaptic AMPA-type glutamate receptors (AMPARs) mediate most fast excitatory synaptic transmission and are crucial for many aspects of brain function, including learning, memory and cognition. The number, synaptic localization and subunit composition of synaptic AMPARs are tightly regulated by network activity and by the history of activity at individual synapses. Furthermore, aberrant AMPAR trafficking is implicated in neurodegenerative diseases. AMPARs therefore represent a prime target for drug development and the mechanisms that control their synaptic delivery, retention and removal are the subject of extensive research. Here, we review recent findings that have provided new insights into AMPAR trafficking and that might lead to the development of novel therapeutic strategies.